Metal‐like Charge Transport in PEDOT(OH) Films by Post‐processing Side Chain Removal from a Soluble Precursor Polymer. (30th November 2022) - Ponder, James F.; Gregory, Shawn A.; Atassi, Amalie; Advincula, Abigail A.; Rinehart, Joshua M.; Freychet, Guillaume; Su, Gregory M.; Yee, Shannon K.; Reynolds, John R.
Abstract: Herein, a route to produce highly electrically conductive doped hydroxymethyl functionalized poly(3, 4‐ethylenedioxythiophene) (PEDOT) films, termed PEDOT(OH) with metal‐like charge transport properties using a fully solution processable precursor polymer is reported. This is achieved via an ester‐functionalized PEDOT derivative [PEDOT(EHE)] that is soluble in a range of solvents with excellent film‐forming ability. PEDOT(EHE) demonstrates moderate electrical conductivities of 20–60 S cm −1 and hopping‐like (i.e., thermally activated) transport when doped with ferric tosylate (FeTos3 ). Upon basic hydrolysis of PEDOT(EHE) films, the electrically insulative side chains are cleaved and washed from the polymer film, leaving a densified film of PEDOT(OH). These films, when optimally doped, reach electrical conductivities of ≈1200 S cm −1 and demonstrate metal‐like (i.e., thermally deactivated and band‐like) transport properties and high stability at comparable doping levels. Abstract : Functionalization of poly(3, 4‐ethylenedioxythiophene) (PEDOT) with ester‐based side chains allows for solution processing and moderate electrical conductivity. Hydrolysis of these side chains leaves hydroxymethyl functional groups on the polymer, increases the relative amount of electroactive material, significantly increases electrical conductivity to greater than 1000 S cm −1, and changes the transport mechanism from hopping‐like to metal‐like.